A new species of planthopper in the genus Colpoptera (Hemiptera:Fulgoroidea: Nogodinidae) from the Caribbean coast of Costa Rica - Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Dam, Alex R. Van; Helmick, Ericka E.; Bartlett, Charles R.; Aponte, Laura V. Martinez; Ruiz, Alfredo Rodriguez; Bloch, Melody; Bahder, Brian W. (Zootaxa, 2024)
A new species of Colpoptera, C. stonei sp. nov., (Colpopterinae: Colpopterini) is described from Costa Rica, during a survey of planthoppers associated with palms. Molecular data for the five-prime region of the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene, and 28S rRNA gene are provided for available members of Colpopterini to support placement in Colpoptera.